The application of Picture Series to improve writing skills - Muhibbudin Muhibbudin (English Education Journal, 2016)
The objective of this study was to investigate the effect of teaching writing by using the picture series technique with second grade students of MTsN Kuta Baro, Aceh Besar. This research was an experimental study. There were two classes selected randomly as the sample of the study, namely the experimental (EG) and the control group (CG). The EG consisted of 26 students whereas, the CG consisted of 24 students. The quantitative data were obtained from the results of the pre-tests and post-tests of the students’ writing. To analyze the data, the means, standard deviations and t-tests were used. The results of the data analysis can be seen from the results of the post-test for each group in which the mean of the post-test scores of the experimental group was 72, while the mean of the post-test scores of the control group is 59. The t-test showed that there was a significant improvement in the students’ writing achievements of the EG compared to the CG. Thus the students taught by using the picture series technique gave a significantly better writing performance than those who were taught by the traditional technique.